Household access to microcredit and children's food security in rural Malawi: A gender perspective - Basudeb Guha-Khasnobis; Gautam Hazarika (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
Using data from the 1995 Malawi Financial Markets and Food Security Survey, this study seeks to discover if women's relative control over household resources or intra-household bargaining power in rural Malawi, gauged by their access to microcredit, plays a role in children's food security, measured by anthropometric nutritional Z-scores. Access to microcredit is assessed in a novel way as self-reported credit limits at microcredit organizations. Since credit limits, that is, the maximum sums that might be borrowed, hinge upon supply-side factors such as the availability of credit programmes and the financial resources of lenders, it is plausible they are more exogenous than demand driven loan uptake or participation in microcredit organizations, the common ways of gauging access to microcredit. It is indicated that whereas the access to microcredit of adult female household members improves 0- to 6-year old girls', though not boys', long-term nutrition as measured by height-for-age, the access to microcredit of males has no such salutary effect on either genders' nutritional status. This may be interpreted as evidence of a positive relation between women's relative control over household resources and young girls' food security. That women's access to microcredit improves young girls' long-term nutrition may be explained in part by the subsidiary finding that it raises household expenditure on food. – microcredit ; gender ; food security ; Malawi
Keywords: J08; J21; I20; J16; 330; Mikrofinanz; Kinder; Ernährung; Landbevölkerung; Malawi